CHANGES IN MEMBRANE CHARACTERISTICS OF HEART MUSCLE DURING INHIBITION - Trautwein, W. (The Rockefeller University Press, 1956)
Membrane characteristics were studied in isolated muscle strands from auricles of frogs using the "square pulse" technique. Changes in the time course and spatial spread of subthreshold electrotonic potentials were measured. If acetylcholine is applied in concentrations which cause slowing or stoppage of the heart beat, the following changes are produced: (a) the length constant (λ) of the membrane is reduced, (b) the time constant is shortened. The effects are reversible and increase with acetylcholine concentration. The membrane changes caused by acetylcholine dimmish with time. It is concluded that during acetylcholine inhibition, as well as during vagal inhibition, the conductance of the muscle membrane is increased. Appreciable changes in the resting membrane potential need not accompany inhibition.